Storage Influence of Apple and Cherry Pollen at Low and Ultralow Temperatures on Its Viability - Safina, G. F.; Tikhonova, N. G.; Verzhuk, V. G.; Shubin, N. A. (Problems of Cryobiology and Cryomedicine, 2005)
The influence of low and ultralow storage temperature on pollen viability of various apple and sour cherry cultivars has been studied. In five months of pollen storage at temperatures about 0°C its viability noticeably decreased. In apple pollen stored at –20°C viability was also reduced in some extent, and vice versa it increased for sour cherry pollen though initially was low. After five months’ storage at –196°C pollen viability for studied apple and sour cherry cultivars in fact did not differ from the initial one. The sour cherry cultivars Elita Rubinovaya was the only exception, as its nearly zero germinating ability has apparently increased after five-month storage at all investigated temperature regimens. Fruit crop pollen cryopreservation is regarded as the most favourable one of all studied storage modes.